2018
DOI: 10.1016/j.ijscr.2018.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and surgical challenges of a giant pheochromocytoma in a resource limited setting—A case report

Abstract: HighlightsGiant pheochromocytomas are rare.Diagnosis requires a high index of suspicion.Commonly present with a triad of headache, palpitations and hypertension.The surgical and anaesthetic team must be prepared to manage hypertensive crisis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
(34 reference statements)
0
10
0
Order By: Relevance
“…Lots of catecholamine will be released in blood, resulting in hypertensive crisis. [4][5][6] In this case, the patient had no obvious continuous hypertension, but only had the vague abdominal sign. The abdominal CT only reminded the huge tumor in the left upper abdominal cavity and behind peritoneum.…”
Section: Discussionmentioning
confidence: 74%
“…Lots of catecholamine will be released in blood, resulting in hypertensive crisis. [4][5][6] In this case, the patient had no obvious continuous hypertension, but only had the vague abdominal sign. The abdominal CT only reminded the huge tumor in the left upper abdominal cavity and behind peritoneum.…”
Section: Discussionmentioning
confidence: 74%
“…In total, 50 published studies were identified by the PubMed search engine when employing the term “PASS pheochromocytoma”. After an initial assessment of eligibility, including the presence of a PASS stratified pheochromocytoma cohort as well as an exclusion of irrelevant studies and reviews, 28 original studies and case reports were initially included in the review [1,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29]. After careful revision of each study, eight additional studies were disqualified from inclusion based on the failure to meet our fourth inclusion criterion of “clearly identified subgroup information (number of tumor samples with and/or without evidence of synchronous or metachronous evidence of malignancy respectively, with the associated PASS score clearly identifiable)” [5,6,8,9,13,14,18,28].…”
Section: Resultsmentioning
confidence: 99%
“…After careful revision of each study, eight additional studies were disqualified from inclusion based on the failure to meet our fourth inclusion criterion of “clearly identified subgroup information (number of tumor samples with and/or without evidence of synchronous or metachronous evidence of malignancy respectively, with the associated PASS score clearly identifiable)” [5,6,8,9,13,14,18,28]. Therefore, a total of 20 studies were included in the meta-analysis [1,3,4,7,10,11,12,15,16,17,19,20,21,22,23,24,25,26,27,29]. These studies and the associated outcomes are detailed in Table 1 and illustrated in Figure 2A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Giant pheochromocytomas are categorized as tumors >7 cm in size [3,7]. Tese giant pheochromocytomas are reported to be rare with just a few case reports published in literature over the past two decades.…”
Section: Introductionmentioning
confidence: 99%